Impact of trade liberalisation on dairy market price co‐movements between the EU, Oceania, and the United States. (19th June 2019) - Rezitis, Anthony N.; Rokopanos, Andreas
Abstract : This study investigates the impact of trade liberalisation on the spatial price co‐movements between the dairy markets of the EU, Oceania, and the United States. We consider two main dairy products, namely butter and whole milk powder (WMP), and employ R‐Vines to assess the development of the tail dependence between the price series. We split the time span (i.e. 2000‐2017) in December 2007 to capture the change in the tail dependence as well as in the potential of each region to act as the central market. Our findings indicate that the EU acts as the central market for butter in both sub‐periods, whereas the EU succeeds Oceania in acting as the central market for WMP from the first sub‐period to the next. Further findings highlight slightly increasing tail dependence in the butter market and in the WMP market for the EU‐OCE and EU‐US pairs. However, the tail dependence for the WMP prices between Oceania and the United States weakens, in which we attribute to the 2013 Chinese ban on milk powder imports from Oceania.